New methods for the synthesis of sulfur functional groups - Ding, M (2023)
Sulfur(VI) functionalities exhibit promising properties for both pharmaceutical and agrochemical applications. Described in this thesis are new methodologies for the synthesis of a range of S(VI) containing compounds, including sulfonimidamides, sulfondiimidoyl fluorides, and sulfondiimidoates. The developed methods exploit sulfinylamine reagents as synthetic linchpins, using organometallic reagents and amines/alcohols as key building blocks, that provide rapid and modular access to these demanding aza-sulfur scaffolds. Chapter 1 is a review introducing sulfur(VI) functional groups, with a focus on the current synthetic methods for accessing sulfonimidamides, sulfondiimidoyl fluorides, and sulfondiimidoates. The properties and applications of these compounds are also considered. Chapter 2 details the discovery of several novel N-silyl sulfinylamines. Notably, a stable sulfinylamine reagent, N-sulfinyltriisopropylsilylamine (TIPS-NSO), enables rapid preparation of primary sulfinamides. A hypervalent iodine-mediated amination of these primary sulfinamides then delivers a diverse range of sulfonimidamides, including a medicinally relevant sulfonimidamide-derivative. Chapter 3 describes the development of a practical synthesis of sulfondiimidoyl fluorides. The route employs organometallic reagents and pre-generated sulfurdiimides as starting materials, proceeding via sulfinamidines, and generating sulfondiimidoyl fluorides with broad structural variation. Divergent syntheses of sulfondiimines and sulfondiimidamides through subsequent SuFEx (sulfur-fluoride exchange) reactions are achieved. Chapter 4 documents a two-step synthetic approach towards sulfondiimidoates, using organometallic reagents, a sulfurdiimide reagent, and alcohols as key components. An iodine(III)-mediated oxidative reaction of primary sulfinamidines directly forms sulfondiimidoates. Variation of the nitrogen substituents of sulfondiimidoates through controlled manipulation is well-tolerated, allowing for the preparation of a series of N-functionalised derivatives. Chapter 5 summaries the research and discusses potential areas for future work. Chapter 6 provides experimental procedures and data for this research.